No Child Left Behind: What About Refugees?. Issue 1 (2nd January 2017) - Moinolnolki, Neda; Han, Myae
Abstract : As populations migrate and seek refuge around the world, educators in receiving countries need information about how to provide meaningful education experiences. Refugee children have higher rates of school dropout and are faced with many challenges, such as acculturation stress, poverty, poor housing, dangerous neighborhoods, and psychological disorders. The purpose of this article is to examine the research and current status of U.S. school system supports for the education of refugee children and to provide suggestions based on evidence-based practice for refugee children's success. The authors provide a historical overview of policies and provisions of refugee education, an assessment of multiple factors affecting refugee children's adjustment and success at school, and a review of evidence-based practice for refugee children.